Redescription and phylogenetic placement of Cirrhilabrus sanguineus Cornic (Teleostei: Labridae), with first documentation of the female form - Tea, Yi-Kai; Frable, Benjamin W.; van Der Wal, Cara (Zootaxa, 2018)
The labrid fish Cirrhilabrus sanguineus Cornic is redescribed on the basis of the neotype, two male specimens, and an additional female specimen recently collected from the northern coast of Mauritius. We provide new live and nuptial colouration descriptions, as well as the first documented female specimen for the species. we also include a molecular phylogenetic analysis of related species, with brief comments on phylogenetic interpretation of putative relationships amongst members of the genus Cirrhilabrus.